2017
DOI: 10.1083/jcb.201701169
|View full text |Cite
|
Sign up to set email alerts
|

Energy landscape differences among integrins establish the framework for understanding activation

Abstract: Li and Springer demonstrate differences between integrins α4β1 and α5β1 in intrinsic affinities and relative free energies of three conformational states. Integrin conformational equilibria are both subunit and cell type specific. The energy landscapes of intact receptors on the cell surface provide a framework for understanding regulation of integrin adhesiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
90
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 59 publications
9
90
1
Order By: Relevance
“…Surface molecules are often linked to cytoskeleton, sitting on the lipid bilayer of the cell membrane, or associated with intracellular signaling molecules. It has been found that the molecular length, dimension and orientation, cell surface roughness, membrane nanostructure, cytoskeleton polymerization, lipid composition, and molecular/cellular signaling can profoundly impact 2D receptor-ligand binding kinetics [11,19,[29][30][31][60][61][62][63][64][65][66]. Several 2D techniques have been used to measure the molecular interactions at live T-cell membranes with pMHCs presented by surrogate APCs or supported planar lipid bilayers.…”
Section: Two-dimensional Tcr Binding Kineticsmentioning
confidence: 99%
“…Surface molecules are often linked to cytoskeleton, sitting on the lipid bilayer of the cell membrane, or associated with intracellular signaling molecules. It has been found that the molecular length, dimension and orientation, cell surface roughness, membrane nanostructure, cytoskeleton polymerization, lipid composition, and molecular/cellular signaling can profoundly impact 2D receptor-ligand binding kinetics [11,19,[29][30][31][60][61][62][63][64][65][66]. Several 2D techniques have been used to measure the molecular interactions at live T-cell membranes with pMHCs presented by surrogate APCs or supported planar lipid bilayers.…”
Section: Two-dimensional Tcr Binding Kineticsmentioning
confidence: 99%
“…Integrins α 4 β 1 , α 5 β 1 , and α V β 6 all appear to have bent-closed, extended-closed, and extended-open conformations. This conclusion is directly demonstrated for α 5 β 1 and α V β 6 by EM (10,11) and may be inferred for α 4 β 1 by the effects of Fabs that stabilize the closed, open, and extended states on affinity of soluble α 4 β 1 fragments for ligands and α 4 β 1 -dependent cell adhesion to specific ligand (6). We therefore interpret the increase in α Values are mean ± SD for one measurement each with Fn3 7-10 , Fn3 8-10 , and Fn3 9-10 , with the exception of the headpiece in Mg 2+ , for which Fn3 7-10 and Fn3 9-10 results could not be fit, and the fit ± fitting error is shown for Fn3 8-10 .…”
Section: Discussionmentioning
confidence: 63%
“…We place our results in the context of recent thermodynamic studies on β 1 integrins that have shown how ligand-binding affinities are regulated by integrin conformational change. Studies on α 4 β 1 and α 5 β 1 showed that affinities of their open conformations were 5,000-fold (α 5 β 1 ) and 700-fold (α 4 β 1 ) higher than their closed conformations and that these affinities were intrinsic, that is, independent of whether the conformation was on the cell surface or in a particular integrin fragment (5,6,10). Differences in affinities among cell-surface integrins and different integrin fragments were caused by differences in relative free energies of conformational states (and their populations) within ensembles in each type of integrin preparations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations